Identification of penicillinase producing Neisseria gonorrhoeae in Chile during clinical and microbiological study of gonococcal susceptibility to antimicrobial agents. Issue 1 (February 1987) - Garcia Moreno, J; Dillon, J R; Arroyave, R; Maldonado, A; Fich, F; Salvo, A; Villalobos, D; Vincent, P; Pauze, M
Abstract : The first penicillinase producing isolates of Neisseria gonorrhoeae (PPNG) identified in Chile were discovered during a clinical and microbiological study to compare the efficacy of penicillin (4.8 MIU aqueous procaine penicillin G plus 1 g oral probenecid) and tetracycline (1.5 g followed by 500 mg four times daily for four days) treatment regimens for acute uncomplicated gonorrhoea. Penicillin treatment was effective in 93.1% (282) of 303 patients, whereas tetracycline was effective in 98.3% (233) of 237 patients. Six of the penicillin treatment failures were attributable to PPNG strains. In all, 21 PPNG strains were identified during the study. They were genetically identical, having a wild type auxotype, a WII/III serotype (serovar Bajk), and carrying cryptic and transfer plasmids and an Asian type penicillinase producing plasmid. In addition, 674 non-PPNG isolates were tested for their susceptibility to eight antimicrobials. Over 95% were sensitivie to 1 mg/l of penicillin, ampicillin, cefotaxime, cefuroxime, and erythromycin, over 90% were sensitive to 1 mg/l of tetracycline and 2 mg/l of thiamphenicol, and all were sensitive to spectinomycin. Of 226 non-PPNG isolates characterised for plasmid content and auxotype, 90% (205) were either wild type or proline requiring, 67% (153) carried only the cryptic plasmid, and a further 31% (71) carried both cryptic and transfer plasmids. Unusually, three of four isolates lacking the cryptic plasmid carried only the transfer plasmid.